2007
DOI: 10.1083/jcb.200706206
|View full text |Cite
|
Sign up to set email alerts
|

EGF-induced PIP2 hydrolysis releases and activates cofilin locally in carcinoma cells

Abstract: Lamellipodial protrusion and directional migration of carcinoma cells towards chemoattractants, such as epidermal growth factor (EGF), depend upon the spatial and temporal regulation of actin cytoskeleton by actin-binding proteins (ABPs). It is generally hypothesized that the activity of many ABPs are temporally and spatially regulated by PIP2; however, this is mainly based on in vitro–binding and structural studies, and generally in vivo evidence is lacking. Here, we provide the first in vivo data that direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
242
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(255 citation statements)
references
References 43 publications
13
242
0
Order By: Relevance
“…Upon addition of rapamycin, rapid reduction of PI(4,5)P 2 and concurrent formation of membrane protrusion were observed ( Fig. 4A and supplemental Video 2), consistent with a recent finding that PLC-dependent PI(4,5)P 2 hydrolysis induced lamellipodia formation (9). This treatment again induced a translocation of Coronin 1A to the extending lamellipodia ( Fig.…”
Section: Pi(45)p 2 Reduction Induces a Translocation Of Coronin 1a Tsupporting
confidence: 90%
See 2 more Smart Citations
“…Upon addition of rapamycin, rapid reduction of PI(4,5)P 2 and concurrent formation of membrane protrusion were observed ( Fig. 4A and supplemental Video 2), consistent with a recent finding that PLC-dependent PI(4,5)P 2 hydrolysis induced lamellipodia formation (9). This treatment again induced a translocation of Coronin 1A to the extending lamellipodia ( Fig.…”
Section: Pi(45)p 2 Reduction Induces a Translocation Of Coronin 1a Tsupporting
confidence: 90%
“…A recent study has reported that Coronin 1B coordinates the activities of Arp2/3 complex and cofilin by recruiting Slingshot, which dephosphorylates and thus activates cofilin (13). In addition, Cofilin is inactivated at the plasma membrane by binding to PI(4,5)P 2 (9). In light of these findings, we propose a plausible mechanism to explain how the cooperated activities of these two actin-depolymerizing factors are spatially and temporally regulated by PI(4,5)P 2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A localized increase in cofilin activity leads to increased numbers of barbed ends for actin polymerization while Arp2/3 promote the nucleation of new filaments [34,35]. Cofilin activity is localized to a region close the plasma membrane because this is the site where PIP2 is hydrolysed and because of its intrinsic preference for recently polymerised ATP-actin filaments [36], while activation of membrane tethered small G proteins leads to increased Arp2/3 activity at the plasma membrane [37,38]. It should also be noted that in other contexts (such as if ADP-actin filaments are severed or other co-operating mechanism are not active) cofilin-mediated filament severing can reduce F-actin levels.…”
Section: Co-operation and Plasticity In Actin Polymerization Mechanismsmentioning
confidence: 99%
“…Furthermore, severed filaments are the preferred substrate for dendritic nucleation by the Arp complex (8,9). Localized induction of actin polymerization and the formation of branched actin networks constitute the basis for membrane protrusion and cell motility (2,10,11). In line with an upstream regulatory role in the control of these processes, PKD1 and -2 are also capable of binding to F-actin in vitro (1).…”
mentioning
confidence: 99%